DETERMINANTS FACTORS ANALYSIS OF INDONESIAN STUDENTS’ PHYSICS ACHIEVEMENT IN TIMSS 2011 - Susongko, P.; Fatkhurrahman, M. A. (Jurnal Pendidikan Fisika Indonesia, 2017)
This study aimed to find the structure of the theoretical model that can illustrate the achievements of Indonesian students in the field of physics. This study also examines the variables that directly or indirectly influence the physics achievement of Indonesian students. The data in this study are data of TIMSS 2011 on physics test with population involved were 4572 Indonesian students grade 8. This research used path analysis from LISREL 8.30. The physics achievement model of Indonesian students based on TIMSS 2011 results are as follows: (1) physics achievement is directly influenced by self-confidence, interest in learning, and students 'attitudes toward the importance of physics; (2) physics achievement indirectly influenced by students' involvement in physics learning indicated from their interest and confidence in physics learning; (3) attitudes toward the importance of physics have an indirectly positive impact on physics achievement. Students' self-confidence in physics learning has a stronger direct influence on their achievements than their interest in physics.